Effect of farnesol on planktonic and biofilm cells of Staphylococcus epidermidis - Gomes, F. I. (2009)
Staphylococcus epidermidis is now amongst the most important pathogenic agents responsible for bloodstream nosocomial infections and for biofilm formation on indwelling medical devices. Its increasing resistance to common antibiotics is a challenge for the development of new antimicrobial agents. Accordingly, the goal of this study was to evaluate the effect of farnesol, a natural sesquiterpenoid, on Staphylococcus epidermidis planktonic and biofilm cells. Farnesol displayed a significant inhibitory effect on planktonic cells. Small concentrations (100 μM) were sufficient to exhibit antibacterial effect on these cells. In biofilm cells the effect of farnesol was not so pronounced and it seems to be strongly dependent on the cells metabolic activity and amount of matrix. Interestingly, the effect of farnesol at 200 μM was similar to the effect of vancomycin at peak serum concentration either in planktonic or biofilm cells. Overall, the results indicate a potential antibacterial effect of farnesol against S. epidermidis, and therefore the possible action of this molecule on the prevention of S. epidermidis related infections.